Mesoscopic Numerical Computation of Compressive Strength and Damage Mechanism of Rubber Concrete - Z. H. Xie; Y. C. Guo; Q. Z. Yuan; P. Y. Huang (Advances in Materials Science and Engineering)
Evaluations of both macroscopic and mesoscopic strengths of materials have been the topic of a great deal of recent research. This paper presents the results of a study, based on the Walraven equation of the production of a mesoscopic random aggregate structure containing various rubber contents and aggregate sizes. On a mesoscopic scale, the damage mechanism in the rubber concrete and the effects of the rubber content and aggregate-mortar interface on the rubber concrete’s compressive resistance property were studied. The results indicate that the random aggregate structural model very closely approximates the experimental results in terms of the fracture distribution and damage characteristics under uniaxial compression. The aggregate-mortar interface mechanical properties have a substantial impact on the test sample’s strength and fracture distribution. As the rubber content increases, the compressive strength and elastic modulus of the test sample decrease proportionally. This paper presents graphics of the entire process from fracture propagation to structural failure of the test piece by means of the mesoscopic finite-element method, which provides a theoretical reference for studying the damage mechanism in rubber concrete and performing parametric calculations.